Service Cooperation Incentive Mechanism in a Dual-channel Supply Chain under Service Differentiation - Jun Chen; Ying Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
An incentive mechanism about service effort provided by the manufacturer in a dual-channel supply chain is studied under asymmetric information. The principal-anent models are developed for asymmetric information and symmetric information, and then the optimal fixed payment and the optimal profit sharing ratio are obtained. In contrast to the case under symmetric information, the conclusion implies that the manufacturer’s profit decreases under asymmetric information, the retailer’s profit keep same even lower service level is provided. Thus, the system performance of the supply chain decreases. http://dx.doi.org/10.11591/telkomnika.v12i12.6193